ASSESSING KNOWLEDGE, ATTITUDE, AND PRACTICE OF HEALTHCARE WORKERS REGARDING MEDICAL WASTE MANAGEMENT AT DISTRICT JAMSHORO, SINDH - BHACHO, AH; CHANNAR , HB; AKHTAR, T; AHMED, A; SIYAL, F; IQRA, . (Biological and Clinical Sciences Research Journal, 2024)
This study aimed to evaluate the waste management knowledge, attitudes, and practices of three groups of healthcare workers: doctors, nurses, and paramedical staff. A cross-sectional study involved doctors, nurses, and technicians at the National Institute of Cardiovascular Disease (NICVD) and the Syed Abdullah Shah Institute of Medical and Health Science (SASIMS) in Shahwan Sharif, District Jamshoro, Sindh. A convenient non-probability sampling technique was used to select the study participants. A total of 370 healthcare workers consented to be part of the study. The data was obtained through the administration of questionnaires. Data were collected and compiled using Microsoft Excel and analyzed using SPSS version 22.0. This study had 39 (63.2%) males and 34 (36.8 %%) females. The median age of participants was 30.5 years, with a mean of 33.12 ± 8.2 years. The majority of the participants were paramedics (42.7%). They were followed by doctors (34.3%) and nurses (23%). The knowledge of healthcare workers indicated that there was a significant association between the waste categories (p = 0.02), type of waste (p = 0.00), color coding differentiation (p = 0.01), hospital policies (p = 0.00), infection control department (p = 0.03), risk toward healthcare workers (p = 0.00), human anatomical waste (p = 0.01), color-coding container used for wasted sharps and infectious solid waste (p = 0.00), and type of color-coding container (p = 0.00) This study highlights the discrepancies and inadequacies of knowledge and practice of proper healthcare waste management among healthcare workers. Healthcare workers with adequate knowledge were paramedics, doctors, and nurses. All healthcare personnel should have medical waste management guidelines ready and easily accessible.